Extraction and characterization of pectin from dragon fruit (Hylocereus polyrhizus) using various extraction conditions. (Pengekstrakan dan pencirian pektin daripada buah naga (hylocereus polyrhizus)menggunakan pelbagai keadaan pengekstrakan) - Norazelina Sah Mohd. Ismail,; Nazaruddin Ramli,; Norziah Mohd. Hani,; Zainudin Meon, (Universiti Kebangsaan Malaysia, 2012)
The extraction of pectin from dragon fruit (Hylocereus polyrhizus) peels under three different extraction conditions was identified as an alternative source of commercial pectin. In this work, dried alcohol-insoluble residues (AIR) of dragon fruit peels were treated separately with 0.25% ammonium oxalate/oxalic acid at a pH of 4.6 at 85oC; 0.03 M HCl at a pH of 1.5 at 85oC; and de-ionized water at 75oC. The pectin obtained from these methods was compared in terms of yield, physicochemical properties and chemical structure. Fourier Transform Infrared Spectroscopy (FTIR) was used in the identification of dragon fruit pectins. The results showed that the pectin yield (14.96-20.14% based on dry weight), moisture content (11.13-11.33%), ash content (6.88-11.55%), equivalent weight (475.64-713.99), methoxyl content (2.98-4.34%), anhydrouronic acid (45.25-52.45%) and the degree of esterification (31.05-46.96%) varied significantly (p < 0.05) with the various extraction conditions used. Pectin extracted with ammonium oxalate gave the highest yield of pectin, with high purity and low ash content. Based on the value of methoxyl content and the degree of esterification, dragon fruit pectin can be categorized as low-methoxyl pectin.